PERAN KOMPETENSI DOSEN DALAM PEMAHAMAN KULIAH AKUNTANSI - Mujilan, Mujilan; Rustiyaningsih, Sri (Widya Warta, 2018)
This study aimed to empirically test the students' perceptions of lecturer competence in the courses they had taken. The research samples were undergraduate accounting students of Economic and Business Faculty Universitas Katolik Widya Mandala Madiun in the academic year of 2016/2017. The samples were obtained by purposive sampling method. Data were collected by distributing the questionnaire directly to the respondents. Hypothesis was tested by multiple regression analysis. The test results showed that the lecturer’s pedagogic competence, the personality competence, the professional competence and the social competence did not affect the level of the students’ understanding on accounting courses. This means that the competency instruments and the understanding of learning methods in students still need further attention. Similarly, synergy is needed among the students, the lecturers, the materials, and the methods used in the learning process.